Dennis Hopper interviews - Hopper, Dennis, 1936-2010.; Dawson, Nick, 1980- (Jackson : University Press of Mississippi, 2012)
The legendary Dennis Hopper (1936-2010) had many identities. He first broke into Hollywood as a fresh-faced young actor in the 1950's, redefined himself as a rebel director with Easy Rider in the late 1960's, and became a bad boy outcast for much of the 1970's. He returned in the 1980's with standout performances in films like Blue Velvet and Hoosiers, was one of the great blockbuster baddies of the 1990's, and ended his career as a ubiquitous actor in genre movies. Hopper, however, was much more than just an actor and director: he was also a photographer, a painter
Dennis Hopper with Tony Shafrazi: Tony Shafrazi / 1999 American Psycho: Lynn Barber / 2001; Dennis Hopper: Interview / 2004; Dennis Hopper Is Riding Easy: Alex Simon / 2008; Additional Resources; Index
Description based upon print version of record.
English
Includes bibliographical references, filmography, and index.
Description based on publisher supplied metadata and other sources.
Keywords: Motion picture actors and actresses -- United States -- Interviews; Motion picture producers and directors -- United States -- Interviews; Hopper, Dennis, -- 1936-2010 -- Interviews